Synthesis, photophysical and anticancer study of D-ring extended estrone analogues1. Issue 84 (16th September 2015) - Maurya, Hardesh K.; Hasanain, Mohammad; Kumar, Ch. Pavan; Vasudeva, Prema G.; Sarkar, Jayanta; Chandrasekharam, M.; Gupta, Atul
<x xml:space="preserve">Abstract</x> A concise route for highly substituted ring extended estrone analogues has been developed. The photophysical and biological study of these compounds revealed their efficacy as possible fluorescence probes in cancer chemotherapy.